Tradition of cultivating bean mixture for multiple benefits and sustainable production system in mountain agriculture : Bean Mixture Cultivation for Sustainable Mountain Farming - Joshi, Bal Krishna; Prasad, Ram Chandrika; Gurung, Rita; Gautam, Subash; Subedi, Anish; Adhikari, Achyut Raj; Karkee, Ajaya; Gauchan, Devendra (SAARC Journal of Agriculture, 2025)
Bean mixture cultivation is a traditional practice in mountain agriculture, though it has been increasingly replaced by monoculture. This survey explored the ecological, cultural, and economic factors driving the widespread adoption of bean mixtures in the Karnali region of Nepal. A household survey consisting of 42 questions was conducted among 34 households in Humla and 40 households in Jumla district. On average, households in Jumla cultivated beans on 1.93 ropani of land, while in Humla, the average area was slightly larger at 2.4 ropani (1 ropani = 0.05 a). In Jumla, 55% of respondents reported cultivating bean mixtures, compared to only 30% in Humla. Jumla farmers cultivated 30 distinct landraces of beans, while Humla farmers grew 12 landraces. In Jumla, 44% of farmers grew mixtures of four landraces, and 5% grew as many as seven landraces. In Humla, 32% of farmers mixed five landraces, 23% mixed three or four, and 11% mixed six landraces. The most commonly grown landraces in Jumla were Kalo Male, Sano Kalo, Rato Male, Rato Sano, and Kalo Sano. In Humla, Kalo Male, Seto Male, and Kalo were the most frequently grown landraces. Most respondents noted that mixed beans have a good taste and reduce the risk of crop failure. Enhancing and promoting bean mixture technology could benefit farmers by increasing ecological yield and supporting agroecological practices. SAARC J. Agric., 22(2): 209-226 (2024)